Experimental droughts with rainout shelters: a methodological review. Issue 1 (17th January 2018) - Hoover, David L.; Wilcox, Kevin R.; Young, Kristina E.
Abstract: Forecast increases in the frequency, intensity, and duration of droughts with climate change may have extreme and extensive ecological consequences. There are currently hundreds of published, ongoing, and new drought experiments worldwide aimed to assess ecological sensitivity to drought and identify the mechanisms governing resistance and resilience. To date, the results from these experiments have varied widely, and thus, patterns of drought sensitivities and the underlying mechanisms have been difficult to discern. Here we examined 89 published drought experiments, along with their associated historical precipitation records to (1) identify where and how drought experiments have been imposed, (2) determine the extremity of drought treatments in the context of historical climate, and (3) assess the influence of ambient precipitation variability on the magnitude of drought experiments. In general, drought experiments were most common in water‐limited ecosystems, such as grasslands, and were often short‐term, as 80% were 1–4 yr in duration. When placed in a historical context, the majority of drought experiments imposed extreme drought, with 61% below the 5th, and 43% below the 1st percentile of the 50‐yr annual precipitation distribution. We also determined that interannual precipitation variability had a large and potentially underappreciated effect on the magnitude of drought treatments due to the co‐varying nature of control and drought precipitation inputs. Thus, detecting significant ecological effects in drought experiments is strongly influenced by the interaction between experimental drought magnitude, precipitation variability, and key ecological thresholds. The patterns that emerged from this study have important implications for the design and interpretation of drought experiments and also highlight critical gaps in our understanding of the ecological effects of drought.